Jawabanmu

2014-05-21T21:11:37+07:00
U1 = 3n - 5
     = 3 - 5
     = -2

U2 = 6 - 5
     = 1

b =U2 -U1
b = 1 - (-2)
b = 3

Sn = n/2 (2a + (n - 1)b)
     = n/2 ( -4 + 3n - 3)
     = n/2 (3n - 7)
     = 3/2 n² - 7/2 n
Sn = 1/2 * (3n^2-7n)
karna polanya adalah Un = 3(n)-5
jadi
U(1) = 3-5 = -2
U(2) = 6-5 = 1
U(3) = 9-5 = 4
jadi dapat disimpulkan beda (b) = 3

Rumus umum,Sn = 1/2(n)*(2(a)+(n-1)*b)
= 1/2(n) * (-4+3n-3)
= 1/2(n)* (3n-7)
Sn => 1/2 * (3n^2-7n)
Komentar sudah dihapus
Komentar sudah dihapus
Komentar sudah dihapus
2014-05-21T21:20:52+07:00
Un=3n-5
misalkan U1= 3(1)-5= -2
              U2= 3(2)-5= 1

Sn= n/2(2a+(n-1)b)
     =n/2(2*(-2)+(n-1)3
     =n/2(-4+3n-3)
     =n/2(3n-7)
     =3/2n^2-7/2n